1-(4-Chlorophenyl)-3-(2-thienylcarbonyl)thiourea - Sohail Saeed; Naghmana Rashid; Wing-Tak Wong (Acta Crystallographica Section E, 2010)
The title compound, C12H9ClN2OS2, exists in the thioamide form with an intramolecular N—H...O hydrogen bond across the thiourea and the carbonyl group. The dihedral angle between the rings is 10.36 (11)°. In the crystal structure, molecules are linked into chains by weak intermolecular C—H...Cl hydrogen-bonding interactions.